2015
DOI: 10.1111/muan.12085
|View full text |Cite
|
Sign up to set email alerts
|

Back to the Future?: Emergent Visions for Object‐Based Teaching in and beyond the Classroom

Abstract: This article introduces a special issue of Museum Anthropology devoted to innovative strategies for teaching with objects. Although a century ago anthropology, museums, and objects were intimately entwined, trends in many museology and anthropology courses have drifted toward focusing on ideas and people rather than objects. The contributors to this special issue have cultivated new pedagogical approaches that complement or realign literaturefocused classroom canons that can distance students from the very obj… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 16 publications
0
6
0
Order By: Relevance
“…Combining the framework of 'object-based learning', frequently used in higher education literature in various domains such as anthropology and science teaching from both cognitive and affective viewpoints (e.g. Adams et al, 2008;Adams, 2015;Schultz, 2018), with disciplinary insights about reasoning with and about historical sources and historical empathy would also be a fruitful way forward. Historical objects in museums, for instance through interrogating their provenance or their (emotional) significance in past and present, are particularly suited to mediate students' historical learning (Bain & Ellebogen, 2002).…”
Section: Conclusion and Discussionmentioning
confidence: 99%
“…Combining the framework of 'object-based learning', frequently used in higher education literature in various domains such as anthropology and science teaching from both cognitive and affective viewpoints (e.g. Adams et al, 2008;Adams, 2015;Schultz, 2018), with disciplinary insights about reasoning with and about historical sources and historical empathy would also be a fruitful way forward. Historical objects in museums, for instance through interrogating their provenance or their (emotional) significance in past and present, are particularly suited to mediate students' historical learning (Bain & Ellebogen, 2002).…”
Section: Conclusion and Discussionmentioning
confidence: 99%
“…This attention is crucial. As Adams (, 89) reminds us, “the recent ‘material turn’ in anthropology has shown that classrooms and exhibition spaces must engage more rigorously and inventively with the fact that humans interact via material things.” Yet, new materialism threatens to “[reintroduce] the binarism between materiality [more specifically, matter] and culture that much work in science studies [and the social sciences] has helped to challenge. Matter becomes a fetish object” (Ahmed , 35).…”
Section: In Theory: Object Orientations In Art and Anthropologymentioning
confidence: 99%
“…The “materialogical imagination” is a material literacy that is simultaneously critical and creative. Many anthropologists recognize that “the teaching of anthropology is enhanced when it embraces sensorial engagement with materiality” (co‐generative human/thing relationships; Adams , 89). The sentiment should extend to collections‐based teaching across disciplines and collection types.…”
Section: Introduction: the Materialogical Imagination As A Twenty‐firmentioning
confidence: 99%
See 1 more Smart Citation
“…If access was the first hurdle SIMA sought to address, methodology, or “what to do when you're there,” was the second. Using objects to teach anthropology has recently received renewed attention, as anthropologists seek to bring object‐based methodologies and analyses into the anthropology classroom (see Adams ). Acquisition of techniques for working with objects relies not only on conceptual tools (Caple ) but also on interactions guided by experts.…”
Section: Perspectives From Sima Studentsmentioning
confidence: 99%